0924 Nighttime Sleep and Daytime Functioning in Ehlers-Danlos Syndrome: A Cohort Study of Syndrome Subtypes. (27th April 2018) - Moss, C; Fernandez-Mendoza, J; Schubart, J; Sheehan, T; Schilling, A; Francomano, C; Bascom, R
Abstract: Introduction: Ehlers-Danlos Syndrome (EDS) is a group of heritable disorders that affect a wide variety of organs and whose pathogenesis involves connective tissue synthesis and regulation. Patients with EDS report fatigue at rates comparable to the more common features of velvety skin, easy bruising, hypermobility, and dysautonomia. However, little is known about the nighttime sleep and daytime functioning correlates, including daytime sleepiness, of patients with well-characterized EDS evaluated with standardized patient-reported outcomes. Methods: A cohort of 252 patients with physician-diagnosed EDS (45.0 ± 16.6y, 73% female, 91% Caucasian) completed the Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS) and Multidimensional Fatigue Inventory (MFI) and underwent a Structured Sleep Medicine Interview. All patients were classified into classical (13%), hypermobile (19%), vascular (27%) or "other" (41%) subtypes. Results: Poor sleep quality (PSQI>5) was present in 61% of patients; 68% reported waking up tired regardless of sleep duration and 33% having insomnia. Daytime fatigue (MFI>12) was present in 45% of patients, while daytime sleepiness (ESS>10) in 31% and severe sleepiness (ESS>15) in 11%. The classical and hypermobile subtypes reported the greatest nighttime and daytime impairments (i.e., poor sleep quality, waking up tired regardless of sleep duration, physical fatigue and severe sleepiness, all Ps<0.05). Poor sleep hygiene practices presented at a low rate, only 19% reported prior polysomnography and 2% currently used CPAP. Conclusion: Patients with EDS have a disproportionately high prevalence of sleep disturbances than expected for the general population. Our novel data unveiled that EDS patients, particularly those with the classical and hypermobile subtypes, not only have significant daytime fatigue but may also suffer from hypersomnia disorders. Given that sleep apnea and poor sleep hygiene cannot entirely explain these high rates of nighttime and daytime impairments, future studies should examine the underlying mechanisms of sleep dysfunction in EDS and each of its geno/phenotypes. Support (If Any): National Institutes of Health NIA/IRP Protocol 2003–086.